IDENTIFICATION OF PERSONALITY PSYCHOTYPE BASED ON IMAGE COMPONENTS - Turdimatov Jakhongirbek Mukhiddin ugli (Bright Mind Publishing, 2025)
This article presents the results of an empirical study conducted to determine a person's psychotype based on the image style. In this case, the image of the person creates a general idea about him, as well as how he sees himself and what others think about him. Image is personal identification, and at the same time, it includes the appearance, behavior, manners, advantages, shortcomings, and other characteristics of a person.
Keywords: Image, psychotype, emotional style, action style, theatrical style, director's style, psychological analysis.